The Influence of Financial Factors on Tax Avoidance in Manufacturing Companies - Apriyanti, Panca; Agustiawan, Agustiawan; Putri, Adriyanti Agustina (Santoso Academy Network, 2024)
The purpose of this study is to investigate how company size, leverage, and profitability affect the likelihood of tax evasion in manufacturing firms that are listed on the Indonesia Stock Exchange. The study employs a quantitative methodology, utilizing secondary data obtained from financial and annual company reports available on the website www.idx.co.id. Using a purposive sampling methodology, 71 sample firms with 284 analytical units were acquired over the course of four years of observation. Multiple regression analysis is the method used for data analysis. The SPSS software, version 25, was used to test the sample. The study's findings indicate that tax avoidance is influenced by profitability, leverage, and company size, based on the outcomes of multiple regression analysis performed at a significance level of 5%. The implications of these findings for managerial decision-making are profound. Managers must be cognizant of the financial factors that influence tax avoidance tendencies within their companies and formulate strategies to optimize tax positions while ensuring compliance with legal and ethical standards. This knowledge empowers managers to make financial structures practices that financial goals and tax obligations.